2019
DOI: 10.1049/iet-nbt.2018.5133
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles using Azadirachta indica leaves: characterisation and impact on Staphylococcus aureus growth and glutathione‐S‐transferase activity

Abstract: Silver nanoparticles (AgNPs) are toxic to various microbes, but the mechanism of action is not fully understood. The present report explores Azadirachta indica leaf extract as a reducing agent for the rapid biosynthesis of AgNPs. The effects of AgNPs on the growth, glutathione-S-transferase (GST) activity, and total protein concentration in Staphylococcus aureus were investigated, as was its antibacterial activity against seven other bacterial strains. Nanoparticle synthesis was confirmed by the UV-Vis spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Here in our proposed work, we have taken the concentration of leaf extract as 3 ml since it effectively worked as an antimicrobial assay at this particular concentration [38]. The obtained results are well match with earlier reported literature [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Characterization and Optimization Of The Green Synthesized N...supporting
confidence: 85%
“…Here in our proposed work, we have taken the concentration of leaf extract as 3 ml since it effectively worked as an antimicrobial assay at this particular concentration [38]. The obtained results are well match with earlier reported literature [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Characterization and Optimization Of The Green Synthesized N...supporting
confidence: 85%
“…44 The polydispersity index (PI) and zeta potential values were recorded using dynamic light scattering (DLS; Brookhaven Instruments). 45 Antibacterial Activity of PF@AgNPs For this study, we selected both gram-negative (E. coli) and gram-positive (B. subtilis and S. aureus) pathogens. Bacterial cultures were activated 24 h prior to the assay.…”
Section: Spectral Analysis Of Pf@agnpsmentioning
confidence: 99%
“…The main problem faced by chemical methods is the use of harmful solvents and reducing agents with costly metal salts [ 19 ]. To overcome these challenges, researchers get encouraged by the biological approach to fabricating nanoparticles by using extracts from organisms such as plants [ 20 ], bacteria [ 21 ], fungi [ 22 ], and algae [ 23 ] for reducing metal salts to metal nanoparticles. The stability of these nanoparticles is enhanced by capping with biomolecules present in the organism [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported biological approaches to nanoparticle production from edible mushrooms [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Edible mushrooms are rich in protein and are enriched with essential amino acids.…”
Section: Introductionmentioning
confidence: 99%